Sleep duration, sleep problems and perceived stress are associated with hippocampal subfield volumes in later life: Findings from The Irish Longitudinal Study on Ageing (TILDA). - Knight, Silvin; Kenny, Rose; Feeney, Joanne; Scarlett, Siobhan (My University, 2021)
Study Objectives: This study examines the cross-sectional and 2-year follow-up relationships between sleep and stress and total hippocampal volume and hippocampal subfield volumes among older adults. Methods: Four hundred seventeen adults (aged 68.8 ± 7.3; 54% women) from the Irish Longitudinal Study on Ageing completed an interview, a questionnaire, and multiparametric brain magnetic resonance imaging. The relationships between self-reported sleep duration, sleep problems, perceived stress, and total hippocampal volume were examined by using ordinary least squares regressions. Linear mixed-effects models were used to investigate the relationships between sleep duration, sleep problems, perceived stress, changes in these measures over 2-years, and hippocampal subfield volumes. Results: No cross-sectional and follow-up associations between sleep and total hippocampal volume and between stress and total hippocampal volume were found. By contrast, Long sleep (≥9–10 h/night) was associated with smaller volumes of molecular layer, hippocampal tail, presubiculum, and subiculum. The co-occurrence of Short sleep (≤6 h) and perceived stress was associated with smaller cornu ammonis 1, molecular layer, subiculum, and tail. Sleep problems independently and in conjunction with higher stress, and increase in sleep problems over 2 years were associated with smaller volumes of these same subfields. Conclusion: Our study highlights the importance of concurrently assessing suboptimal sleep and stress for phenotyping individuals at risk of hippocampal subfield atrophy.
PUBLISHED
Keywords: Ageing